(untitled) (The Research of Medical Science Review, 2024)
Background: Social media has turn out to be a pervasive issue of teens' lives, extensively influencing their mental health. Objectives: This study examines the connection among social media utilization and anxiety issues in young adults, focusing on display time, Fear of Missing Out (FOMO), and social comparisons. Methodology: A cross-sectional study carried out with three hundred teens using validated scales to evaluate anxiety level, FOMO, and social media behaviors. Descriptive and inferential analyses had been performed to discover correlations and patterns. Results: Teenagers spending greater than 3 hours every day on social media said extensively better anxiety degrees, with FOMO and on-line comparisons as sturdy predictors. Conclusion: Excessive social media utilization contributes to heightened tension in young adults, emphasizing the need for focus and interventions to inspire more healthy virtual behavior. These findings can inform strategies to mitigate the mental fitness dangers associated with social media use.